Films and Children: A Study of Korean Film Consumer Legal Protection - Kelik Wardiono; Imaniar Rinanda Ayuningtyas (Universitas Muhammadiyah Sumatera Utara, 2022)
This research, which aims to describe the legal protection of children as consumers of Korean films, is based on legal research with a doctrinal approach. The main data in this study is in the form of secondary data obtained through a literature study on Korean films broadcast via the Netflix platform. Based on the discussions that have been carried out, it is known that Korean films still do not provide legal protection for children as film consumers, this is evidenced by the many scenes that conflict with Article 6 of Law Number 33 of 2009 concerning Film, such as scenes containing violence, the use of narcotics, pornography and scenes that can degrade human dignity